Artificial skin silicone composite material for humanoid robot and preparation method and application thereof

CN122978728APending Publication Date: 2026-10-27XIAMEN SHUNXIN NEW MATERIALS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611112272.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-24
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

其中,热固性硅橡胶(如加成型或过氧化物硫化硅橡胶)具有优异的柔韧性、耐候性和生物相容性,但其硬度通常难以降至极低(如邵氏A 0-5度),且加工成型周期长,废料不可回收,限制了其在追求极致仿生触感和绿色制造中的应用

Benefits of technology

(1)本发明所提供的用于人形机器人的人工皮肤硅胶复合材料性能集成卓越:成功实现了邵氏硬度0A-5A的超软亲肤触感、高灵敏度应变感知、优异环境防护(耐紫外、抗撕裂)以及良好加工性的多重性能一体化。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The application discloses an artificial skin silicone composite material for a humanoid robot, which is composed of a dynamic cross-linking silicone matrix and a multifunctional conductive sensing network, and has a functional gradient or a multi-layer structure; wherein the dynamic cross-linking silicone matrix is composed of a siloxane polymer network containing reversible covalent bonds or supramolecular forces; the multifunctional conductive sensing network is a three-dimensional connected and oriented network structure formed by field-induced assembly of surface-modified one-dimensional or two-dimensional nano-conductive fillers in the dynamic cross-linking silicone matrix; the surface of the surface-modified one-dimensional or two-dimensional nano-conductive fillers is grafted with a polymer brush with a "double-end anchoring and intermediate flexibility", and in the multifunctional conductive sensing network, at least part of the one-dimensional conductive fillers are surface-modified with a soft insulating polymer layer with a thickness of 1-5 nm. The application further discloses a preparation method of the artificial skin silicone composite material for the humanoid robot.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of polymer materials technology, and in particular to a silicone composite material for artificial skin of humanoid robots, its preparation method and application. Background Technology

[0002] With the rapid development of humanoid robot technology, "artificial skin," as a key interface for human-computer interaction, is evolving from a simple physical covering layer into "hyper-bionic skin" that integrates multiple functions such as perception, interaction, and protection. Ideal robot skin should not only possess the softness and dry feel of real human skin, but also be able to sensitively sense various external stimuli such as pressure, stretching, and temperature, and have good resistance to environmental aging and mechanical damage.

[0003] Currently, the mainstream materials used for humanoid robot skin include thermosetting silicone rubber and thermoplastic elastomers (TPE). Among them, thermosetting silicone rubber (such as addition-type or peroxide-cured silicone rubber) has excellent flexibility, weather resistance, and biocompatibility, but its hardness is usually difficult to reduce to extremely low levels (such as Shore A 0-5), and the processing and molding cycle is long, with waste that cannot be recycled, limiting its application in pursuing ultimate biomimetic touch and green manufacturing. In addition, when adding conductive fillers (such as carbon black, carbon nanotubes, and silver nanowires) to silicone through simple blending to impart sensing functions, problems such as uneven filler dispersion, weak interfacial bonding, and easy failure of the conductive network under high strain are usually encountered, resulting in low sensing sensitivity and unstable signals.

[0004] On the other hand, while thermoplastic elastomers (TPEs) or silicone-based thermoplastic vulcanizates (SiTPVs) can achieve lower hardness and a dry touch, and support thermoplastic processing, their long-term mechanical stability, creep resistance, and load-bearing capacity for high-content functional fillers are insufficient. More importantly, existing material systems are mostly homogeneous composites or simple laminated structures, making it difficult to optimize surface feel, internal sensing, and overall protective performance within the same system, resulting in low functional integration. In terms of processing, traditional processes struggle to achieve precise and orderly arrangement of conductive fillers in three-dimensional space, making it impossible to construct anisotropic high-performance sensing networks. Furthermore, there is a fundamental contradiction between the recyclability of materials and their dimensional stability and durability under service conditions.

[0005] Therefore, there is an urgent need to develop a novel material system and manufacturing method to systematically resolve the multiple contradictions between ultra-soft touch, high functional integration, stable durability, and green processing, and to meet the high-performance requirements of next-generation humanoid robot bionic skin. In view of this, this patent application is hereby filed. Summary of the Invention

[0006] The purpose of this invention is to provide a silicone composite material for artificial skin of humanoid robots, its preparation method and application.

[0007] To achieve the above objectives, the solution of the present invention is: A silicone composite material for artificial skin of humanoid robots, the composite material being composed of a dynamically cross-linked silicone matrix and a multifunctional conductive sensing network, having a functionally graded or multilayer structure; wherein, the dynamically cross-linked silicone matrix is ​​composed of a siloxane polymer network containing reversible covalent bonds or supramolecular interactions; the multifunctional conductive sensing network is a three-dimensional interconnected and oriented network structure formed by surface-modified one-dimensional or two-dimensional nano-conductive fillers in the dynamically cross-linked silicone matrix through external field-induced assembly. Furthermore, the dynamically cross-linked silicone matrix comprises two dynamic networks with different response characteristics: the first network is composed of dynamic covalent bonds; the second network is composed of thermosensitive supramolecular forces.

[0008] Furthermore, the dynamic covalent bonds in the first network are selected from at least one of dynamic covalent bonds based on transesterification reactions, reversible covalent bonds based on Diels-Alder addition reactions, and dynamic covalent bonds based on disulfide bond exchange.

[0009] Furthermore, the thermosensitive supramolecular forces in the second network are selected from at least one of the following: quadruple hydrogen bonds based on 2-ureido-4[1H]-pyrimidinone, supramolecular interactions based on coordination bonds, and forces based on the melting-crystallization phase transition of crystalline soft segments.

[0010] Furthermore, the insulating polymer layer is discontinuously distributed on the filler surface.

[0011] Furthermore, the conductive filler in the multifunctional conductive sensing network is a core-shell hybrid filler.

[0012] A method for preparing the silicone composite material for artificial skin of a humanoid robot includes the following steps: (1) Surface modification and pretreatment of conductive fillers: The selected nano-conductive fillers are surface functionalized to introduce reactive functional groups that can chemically bond or strongly interact with the dynamic silica network. (2) Preparation of dynamically crosslinked silicone prepolymers: Synthesize siloxane prepolymer compositions containing reversible covalent precursors or supramolecular units; (3) Preparation of filler-matrix composite slurry: The modified conductive filler obtained in step (1) is uniformly dispersed in the dynamic cross-linked silicone prepolymer obtained in step (2) to form a processable composite slurry; (4) External field-induced directional assembly and molding: The composite slurry obtained in step (3) is injected or coated onto the molding mold or substrate. Before or during the curing process of the slurry, a specific external field is applied to induce the conductive filler to be oriented and assembled in a preset direction to form an orderly conductive network. (5) Dynamic cross-linking curing and post-treatment: Under suitable temperature or light conditions, the prepolymer in step (4) undergoes a cross-linking reaction to form a dynamic cross-linking network, while locking the ordered structure of the filler.

[0013] Furthermore, the surface functionalization modification described in step (1) includes grafting a polymer brush with "double-ended anchoring and intermediate flexibility" onto the surface of the conductive filler.

[0014] Furthermore, the external field mentioned in step (4) is at least one of a magnetic field, an electric field, or a shear field.

[0015] A humanoid robot bionic skin, said humanoid robot bionic skin is made of the aforementioned silicone composite material.

[0016] The principle of the artificial skin silicone composite material for humanoid robots and its preparation method provided by this invention is as follows: The main concept of the silicone composite material for artificial skin of humanoid robots designed in this invention is as follows: First, addressing the challenge of weak interfacial bonding between the filler and the matrix, we designed a polymer brush with "double-ended anchoring and intermediate flexibility" grafted onto the surface of the conductive filler. Specifically, one end of the designed polymer brush can achieve strong covalent anchoring with the filler surface through multiple dynamic covalent bonds (e.g., multiple disulfide bonds), while the other end is modified with functional groups that can reversibly covalently bond with the dynamic silicone network (e.g., furanyl or maleimide groups for Diels-Alder reactions) or form strong supramolecular interactions (e.g., UPy-based quadruple hydrogen bonds); the intermediate segment is a highly flexible polymer segment (e.g., polydimethylsiloxane, PDMS). This design constructs an elastic interfacial transition layer between the filler and the matrix that possesses both high strength and high ductility. When the matrix undergoes large deformation, this interfacial layer can adapt through the reversible breaking and recombination of dynamic bonds, allowing the filler to undergo a certain displacement without debonding, thereby maintaining the stability of the conductive pathway under large strain cycles. Secondly, the silicone composite material provided by this invention designs a dynamically cross-linked silicone matrix comprising two dynamic networks with different response characteristics: the first network is a basic stable network composed of dynamic covalent bonds with high activation energies, such as transesterification bonds based on specific catalysts or thermally reversible Diels-Alder bonds. This network remains relatively stable within the conventional operating temperature range of robotic skin (-10-60℃), providing basic mechanical strength and creep resistance. The second network is a thermo-responsive modulating network composed of thermosensitive supramolecular forces, such as tetrahydrogen-bonded dimers based on 2-ureido-4[1H]-pyrimidinone (UPy), or crystalline soft segments (such as long-chain alkanes) with a certain melting point. This network dissociates or melts at processing temperatures (e.g., 100-130℃), greatly reducing network viscosity and imparting excellent thermoplastic flowability to the material; when the temperature drops to the operating temperature, supramolecular forces recombine or crystallize, significantly enhancing the instantaneous modulus and dimensional stability of the material. This "temperature-gated" design enables intelligent switching of material properties, perfectly improving the processing efficiency and reliability of silicone composite materials. Third, to achieve highly sensitive and stable strain sensing, the silicone composite material provided by this invention also features a special modification to the one-dimensional conductive filler (preferably silver nanowires), coating its surface with an extremely thin (1-5 nm) layer of flexible polydopamine insulating polymer; the polydopamine insulating layer has good compatibility with the silicone matrix. In the unstrained state, the silver nanowires approach each other, and electrons tunnel through the polydopamine insulating layer via quantum tunneling, forming a conductive path. When the material is stretched, the spacing between the silver nanowires increases, and the tunneling resistance increases exponentially, thus achieving highly sensitive resistance changes.Because the conductivity mechanism relies on the tunneling effect rather than the direct physical contact of the fillers, even if the fillers slip relative to each other under large strain, the resistance change is continuous and highly reversible as long as the insulating layer remains in contact. This solves the problem of easy failure of traditional contact-type conductive networks. Fourth, in the preparation of the silicone composite material, to achieve a strong and integrated bond of the multilayer functional structure, this invention introduces an interfacial transition slurry containing a two-component reactive resin between the layers. During co-extrusion or sequential coating, this slurry is injected between adjacent layers. In subsequent heat treatment, resin A forms a locally interpenetrating network (IPN) with the upper layer material and resin B forms a locally interpenetrating network (IPN) with the lower layer material, while cross-linking reactions also occur between resin A and B. Ultimately, a gradient transition zone with continuously varying chemical composition and modulus is formed in the interfacial region, rather than a clear physical interface. This endows the composite material with extremely high interlayer peel strength (>50 N / cm) and excellent fatigue resistance.

[0017] The advantages of the artificial skin silicone composite material for humanoid robots and its preparation method provided by this invention are as follows: (1) The artificial skin silicone composite material for humanoid robots provided by this invention has excellent integrated performance: it successfully achieves multiple integrated properties such as ultra-soft skin-friendly touch with Shore hardness of 0A-5A, high sensitivity strain sensing, excellent environmental protection (UV resistance, tear resistance) and good processability.

[0018] (2) The artificial skin silicone composite material for humanoid robots provided by the present invention has strong and durable interface bonding: through dynamic adaptive interface layer and gradient IPN interface technology, it ensures a strong bond between filler and matrix, and between functional layers under long-term dynamic load, effectively solving failure problems such as delamination and debonding.

[0019] (3) The silicone composite material for artificial skin of humanoid robots provided by the present invention has broad application prospects: The material of the present invention is not only suitable for humanoid robot skin, but can also be widely used in flexible wearable devices, medical rehabilitation devices, intelligent prostheses, high-end consumer electronics and other fields, with huge market potential and technical value. Detailed Implementation

[0020] The present invention will be further described in detail below with reference to embodiments. It should also be understood that the following embodiments are only for further illustration of the present invention and should not be construed as limiting the scope of protection of the present invention. The specific mass, reaction time, temperature, process parameters, etc., in the examples are merely examples within a suitable range. Any non-essential improvements and adjustments made by those skilled in the art based on the above description of the present invention are within the scope of protection of the present invention.

[0021] Unless otherwise specified, all reagents used are commercially available and were not further purified before use.

[0022] The monomer 2-ureido-4[1H]-pyrimidinone isocyanate (UPy-NCO) used in some embodiments of this invention is a non-commercial reagent, and the specific synthesis steps are as follows: Add 80g HDI, 1.5g dibutyltin dilaurate, and 100ml toluene to a dry four-necked flask equipped with a stirrer, thermometer, condenser, and nitrogen inlet tube. Then turn on the nitrogen and slowly purge for 10 minutes to displace the air in the reaction flask while maintaining a slight positive nitrogen pressure. While stirring, heat the reaction system to 60°C and add 50g 6-methylisocytosine (ground into powder, added in 5 portions of 10g each, over approximately 1 hour). After the 6-methylisocytosine is added, heat the reaction system to 80°C and continue the reaction at this temperature for 4 hours. Then stop heating, cool the reaction solution to room temperature, and distill under reduced pressure to remove the solvent toluene and unreacted HDI. The resulting pale yellow, viscous liquid product is UPy-NCO.

[0023] The Maleimide-PDMS-Thiol used in some of the embodiments of this invention is a non-commercial reagent, and the specific synthesis steps are as follows: (1) Add 25 g of amino-terminated polydimethylsiloxane APDMS (Mn(PDMS) = 10 kDa) and 150 mL of anhydrous 2-methyltetrahydrofuran to a 250 mL double-necked round-bottom flask. Stir at room temperature until completely dissolved, then add maleic anhydride (0.49 g, 0.005 mol, slightly in excess). Heat to 40 °C under N2 protection and stir for 48 hours. After the reaction is completed, wash the reaction solution with saturated NaCl solution (3 × 50 mL), saturated NaHCO3 solution (1 × 50 mL), and deionized water (3 × 50 mL) in sequence. Dry with MgSO4, filter, and remove the solvent by rotary evaporation to prepare Maleamic Acid PDMS (MA-PDMS-MA). (2) The MA-PDMS-MA obtained in step (1) was dissolved in 150 mL of anhydrous 2-methyltetrahydrofuran, and then acetic anhydride (0.47 mL, 0.005 mol) and triethylamine (0.70 mL, 0.005 mol) were added in sequence. The reaction system was heated to 60 °C and stirred for 48 hours. After the reaction was completed, the reaction solution was washed with saturated NaCl solution (3×50 mL), saturated NaHCO3 solution (1×50 mL), and deionized water (3×50 mL) in sequence. The solution was dried with MgSO4, filtered, and the solvent was removed by rotary evaporation. The resulting concentrated solution was added to 40 mL of cold methanol (-20 °C) to precipitate and prepare Maleimide-PDMS-Maleimide. (3) Dissolve 5.0 g of Maleimide-PDMS-Maleimide obtained in step (2) in 40 mL of anhydrous dichloromethane, then add 0.4 g of S-triphenylmethyl-L-cysteine, and stir the resulting mixture at room temperature for 1.5 hours. After the reaction is complete, remove the solvent by rotary evaporation, add the resulting concentrate to 25 mL of cold methanol (-20℃) to precipitate, dry the precipitate under vacuum, and dissolve it in 20 mL of TFA / Et3SiH / DCM mixture (volume ratio 90:5:5). Stir at room temperature for 1 hour, remove most of the TFA by rotary evaporation, add the resulting concentrate to 25 mL of cold methanol (-20℃) to precipitate, and dry the precipitate under vacuum to prepare Maleimide-PDMS-Thiol.

[0024] The preparation steps of the oleic acid-modified Fe3O4 nanoparticles used in some embodiments of this invention are as follows: 2.1 g FeCl3·6H2O and 4.7 g sodium oleate were dissolved in a mixed solvent consisting of 45 mL water, 40 mL ethanol, and 40 mL n-hexane. The resulting mixture was stirred at 70 °C for 2.5 hours. After the reaction, the upper n-hexane layer turned brownish-red (containing iron oleate), and the lower layer was a colorless / pale yellow aqueous phase. The upper organic phase was separated using a separatory funnel, and the n-hexane was removed by rotary evaporation. The resulting solid was redissolved in 10 mL of 1-octadecene, and then 1 mL of oleic acid was added. The resulting mixture was transferred to a stainless steel autoclave (with a polytetrafluoroethylene liner), sealed, and hydrothermally reacted at 200 °C for 10 hours. After the reaction, the product was separated using a magnet, washed three times with ethanol and acetone, and dried under vacuum at 60 °C. Example 1: The fabrication conditions and steps for anisotropic sensing thin films based on DA / UPy dual dynamic networks and CNT dynamic adaptive interfaces are as follows: The raw materials and reagents used include: hydroxyl-terminated polydimethylsiloxane (PDMS-OH, Mn=5000 g / mol), furan-2-ylmethyl isocyanate, α,ω-diaminopropyl polydimethylsiloxane (NH2-PDMS-NH2, Mn=3000 g / mol), 2-ureido-4[1H]-pyrimidinone isocyanate UPy-NCO, dibutyltin dilaurate (DBTDL), multi-walled carbon nanotubes (MWCNT, diameter 10-20 nm, length 10-30 μm), 3-mercaptopropyltrimethoxysilane (MPTMS), Maleimide-PDMS-Thiol, triethylamine (TEA), tetrahydrofuran (THF), toluene, and N,N-dimethylformamide (DMF).

[0025] The specific experimental steps for preparing dynamically adaptive interface-modified CNTs (CNT@Mal-PDMS) are as follows: (1) 1.0 g of MWCNT was added to 80 mL of mixed acid (concentrated H2SO4:concentrated HNO3=3:1 v / v), ultrasonically dispersed for 30 minutes, and then heated in an oil bath at 60℃ for 4 hours. After cooling, it was diluted with 100 mL of deionized water, centrifuged, and washed with deionized water until neutral. After freeze-drying, acidified CNT (CNT-COOH) was prepared. (2) Disperse 0.5 g of CNT-COOH obtained in step (1) in 50 mL of DMF / toluene (1:1) mixed solvent and sonicate for 1 hour; then add 2.0 g of MPTMS and 0.05 g of AIBN, and react at 70 °C for 24 hours under nitrogen protection; after the reaction is completed, centrifuge, wash the obtained solid three times with 25 mL of anhydrous ethanol, and vacuum dry to prepare thiolized CNT (CNT-SH). (3) Disperse 0.3 g of CNT-SH obtained in step (2) in 30 mL of dry THF, then add 0.6 g of Maleimide-PDMS-Thiol and 0.3 mL of TEA. Stir the mixture at room temperature for 12 hours. After centrifugation, wash the solid obtained three times with 20 mL of THF and dry it under vacuum to obtain the final product CNT@Mal-PDMS.

[0026] The steps for preparing the furan / UPy dual dynamic network prepolymer are as follows: (1) In a dry three-necked flask, add 10 g PDMS-OH (2 mmol) and 0.58 g furan methyl isocyanate (4.4 mmol, 10% excess), add 0.01 g DBTDL, react at 60 °C for 6 hours under nitrogen protection, and then monitor the NCO characteristic peak (2270 cm⁻¹) by FT-IR. -1 The disappearance of the reaction confirmed the complete preparation of furan-terminated PDMS (F-PDMS-F). (2) Weigh out 6 parts of F-PDMS-F, 2 parts of NH2-PDMS-NH2, 1 part of UPy-NCO, 1 part of PDMS oil (Mn=10000), and 0.005 parts of DBTDL obtained in step (1) by weight ratio; add all raw materials into a planetary mixer and mix and stir for 1 hour at 50°C and vacuum (-0.095 MPa) to obtain a uniform and viscous light yellow prepolymer, which is the furan / UPy dual dynamic network prepolymer; The steps for preparing the composite thin film are as follows: (1) 0.15 g CNT@Mal-PDMS (accounting for 1.5 wt% of the total prepolymer) was added to 10 g of furan / UPy dual dynamic network prepolymer; at the same time, 0.025 g of oleic acid modified Fe3O4 nanoparticles were added; the resulting mixture was added to a planetary mixer and mixed and stirred at 50 °C and vacuum (-0.095 MPa) for 2 hours to obtain a uniform black magnetic composite slurry; (2) Pour the black magnetic composite slurry obtained in step (1) into a square polytetrafluoroethylene (PTFE) mold (100 mm × 100 mm). Place the mold above an electromagnet platform that can generate a uniform gradient magnetic field (the magnetic field direction is parallel to one side of the mold, set as the X direction, and the magnetic field strength is 0.3 T). Preheat in an 80°C oven for 5 minutes to reduce viscosity, then turn on the magnetic field and maintain it for 10 minutes. Then transfer the mold to a 120°C oven and cure for 2 hours. During this process, the furan group of F-PDMS-F undergoes a DA reaction with the maleimide group on CNT@Mal-PDMS, and at the same time, the furan group of F-PDMS-F also reacts with the amino group of NH2-PDMS-NH2 (through Michael addition). The UPy unit forms hydrogen bonds during the cooling process. After curing, allow it to cool naturally to room temperature and demold to obtain a black elastic film with a thickness of about 0.3 mm.

[0027] The thin film performance tests and results are as follows: The hardness was tested using a Shore A hardness tester, and the result was 3 A.

[0028] The electrical conductivity and anisotropic sensing properties of the hardness were tested using a four-probe resistivity meter and a universal testing machine; the results showed that the initial resistivity of the prepared thin film along the X-direction (filler orientation direction) was 2.1 × 10⁻⁶. 3 Ω / sq; the surface resistance along the perpendicular Y direction is 8.5 × 10 Ω / sq. 4 The film exhibits significant anisotropy with a strain of Ω / sq. In the 0-200% strain range, GF ≈ 15; in the 200%-600% strain range, GF increases to approximately 65. When stretched along the Y direction, GF remains below 2 within the 0-600% strain range.

[0029] Cyclic stability test: Cyclic tensile test with strain of 0-500% was performed along the X direction at a frequency of 0.1 Hz. After 10,000 cycles, the resistance response curve showed good overlap with the initial curve, and the fluctuation of the maximum resistance change was less than 5%.

[0030] Dynamic thermomechanical analysis (DMA): Tests show that the material exhibits a significant modulus decrease at approximately 75°C, corresponding to the dissociation of UPy hydrogen bonds; the modulus decreases sharply again at approximately 120°C, corresponding to the reversible opening of DA bonds; indicating that a temperature-gated dual dynamic network has been successfully constructed.

[0031] Example 2 The preparation conditions and steps of the AgNW@PDA quantum tunneling sensing layer and gradient IPN three-layer composite skin sheet are as follows: The raw materials and reagents used include: dynamic silica gel prepolymer (same formulation as in Example 1), silver nanowires (AgNW, diameter 80±20 nm, length 20-50 μm, dispersed in ethanol), dopamine hydrochloride, Tris-HCl buffer (pH=8.5), carbon black (CB, particle size 30 nm), chopped aramid fibers (length ~100 μm, diameter 12 μm), MQ silicone resin (tackifier), hydrogen-containing silicone oil (crosslinking agent), platinum catalyst (Karstedt catalyst), acrylate-terminated polyurethane prepolymer (resin A, trade name CN9010), epoxy-terminated polydimethylsiloxane (resin B, trade name DMS-E12), perfluorooctyl ethyl acrylate (FOEA), Irgacure 184, KH570, and HFE-7100 (for surface treatment).

[0032] The experimental steps for preparing composite skin sheets are as follows: The specific experimental steps for preparing AgNW@PDA are as follows: Take 20 mL of AgNW ethanol dispersion (solid content 1 wt%), centrifuge to remove ethanol, and redisperse in 200 mL Tris-HCl buffer (pH=8.5); then add 0.1 g of dopamine hydrochloride, and stir the resulting mixture at room temperature in the dark for 24 hours; after centrifugation of the reaction product, wash the resulting solid with 10 mL of deionized water more than 5 times to obtain AgNW@PDA, and redisperse the prepared AgNW@PDA in 20 mL of ethanol for later use; it should be noted that by controlling the amount of dopamine hydrochloride added (0.1 g corresponds to 20 mg AgNW) and the reaction time (24 hours), PDA can form discontinuous island or network coatings on the AgNW surface, rather than a dense continuous layer, thereby providing a tunneling effect while leaving sites for possible subsequent polymer brush grafting.

[0033] The specific experimental steps for preparing the three-layer composite sheet are as follows: (1) Preparation of the three-layer main material formula: Surface material: Take 10 g of dynamic silicone prepolymer (same as in Example 1), add 3 g of methyl silicone oil (plasticizer), 0.2 g of hydrophobic vapor phase SiO2, and 0.02 g of platinum catalyst, and mix evenly; (2) Intermediate layer material (sensing layer): Take 10 g of dynamic silica gel prepolymer, add 2 mL of AgNW@PDA ethanol dispersion (containing about 0.02 g of AgNW), 0.1 g of CB, and 0.02 g of platinum catalyst, and mix evenly after removing the ethanol by vacuum stirring; (3) Bottom material (protective layer): Take 10 g of dynamic silicone prepolymer, add 0.5 g of chopped aramid fiber, 0.3 g of MQ resin, 0.15 g of hydrogen-containing silicone oil (molar ratio of Si-H:Vi to vinyl in the prepolymer is 1.5:1), and 0.02 g of platinum catalyst, and mix evenly; (4) Interfacial layer resin solution: Mix resin A and resin B in a 1:1 weight ratio and dilute with ethyl acetate to a solid content of 20%; (5) Co-extrusion process: A laboratory three-layer co-extrusion casting test machine was used; three micro extruders plasticized the three main materials respectively and merged into the three-layer co-extrusion T-die (die lip width 200 mm, gap adjustable); in the laminar flow confluence area inside the die, the interface layer resin solution was injected into the surface layer or the middle layer, or the middle layer or the bottom layer respectively through two precision injection pumps, and the injection rate was controlled at 1% of the main material extrusion rate; (6) Casting and Curing: The co-extruded molten sheet is cast onto a PET release film moving at a uniform speed and passed through a three-stage heating tunnel: the first stage is 80°C for 30 seconds (preheating); the second stage is 120°C for 2 minutes (main curing stage, where hydrosilylation reaction and interfacial resin reaction occur); the third stage is 150°C for 30 seconds (post-curing). Finally, a three-layer composite sheet with a thickness of about 0.5 mm (top layer 0.1 mm, middle layer 0.2 mm, bottom layer 0.2 mm) is obtained and peeled off from the release film; (7) Superoleophobic treatment: Dissolve 8 parts of perfluorooctyl ethyl acrylate (FOEA) monomer, 0.5 parts of photoinitiator Irgacure 184 (0.5-1 wt%), and 1.5 parts of silane coupling agent KH570 in 100 parts of hydrofluoroether (HFE-7100) solvent to prepare a superoleophobic treatment solution; then spray the prepared superoleophobic treatment solution onto the three-layer composite sheet prepared in step (6), and immediately place the obtained sample in a nitrogen atmosphere chamber and irradiate it with a 365 nm ultraviolet LED surface light source for 40 seconds (light intensity about 50 mW / cm). 2 Once curing is complete, a three-layer composite sheet with a superoleophobic surface treatment can be prepared.

[0034] The performance of the prepared three-layer composite sheet was tested, and the results are as follows: Interlayer bonding strength: 90° peel test (refer to ASTM D6862), the peel strength between the top layer and the middle layer, and between the middle layer and the bottom layer are all greater than 60 N / cm, and the failure occurs in the material bulk rather than at the interface, indicating that the gradient IPN interface bonding is extremely strong.

[0035] Surface properties: The surface layer has a Shore hardness of 2 A; the water contact angle is 115° and the hexadecane contact angle is 152°, meeting the superoleophobic standard; after rubbing with a cotton cloth bearing a 100g load for 100 cycles, the hexadecane contact angle is still greater than 145°, showing good wear resistance.

[0036] Sensing performance: Volume resistivity: The intermediate layer is approximately 8 × 10⁻⁶. 2 Ω·cm. Strain sensitivity: In-plane tensile tests were performed on the composite sheet. Due to the quantum tunneling effect of AgNW@PDA, the resistance change is continuous and smooth without abrupt changes across the entire strain range of 0-800%. The GF value is approximately 40 in the 0-300% strain range and rises to approximately 220 in the 300%-800% strain range, exhibiting extremely high sensitivity.

[0037] Multi-cycle testing: Cyclic testing was conducted from 0 to 500% strain. After 5000 cycles, the zero-point resistance drifted by 88%, indicating that the dynamic network was successfully reassembled.

[0038] Protective performance: Tear strength (ASTM D624): up to 25 kN / m.

[0039] UV aging: Place the sample in a UV aging chamber (UVA-340 lamp, 0.7 W / m²). 2 After irradiation at 340nm (60℃) for 500 hours, the tensile strength retention rate was 92%, the elongation at break retention rate was 90%, and the volume resistivity change was <8%.

[0040] Adhesion performance: The bottom layer of the composite sheet was bonded to the aluminum alloy plate (after grinding and cleaning) with room temperature vulcanizing silicone rubber. After curing, the 180° peel strength was tested and reached 18 N / cm.

[0041] Example 3 Validation of recycling and reprocessing of dynamically cross-linked silicone composite materials The raw materials and reagents used include: CNT composite film scraps prepared in Example 1; three-layer composite sheet scraps prepared in Example 2; tetraisopropyl titanate (Ti(OiPr)4).

[0042] The specific experimental steps are as follows: (1) Crushing: After freezing the two types of scrap materials with liquid nitrogen, they are crushed in a pulverizer and sieved to obtain particles with a particle size of 1-3 mm. (2) Mixing and adding catalyst: Mix the two crushed materials in a 1:1 weight ratio; take 10 g of the mixture, add 0.05 g Ti(OiPr)4 (0.5 wt%), stir manually in a beaker to initially mix, and then use a high-speed mixer to mix for 2 minutes to ensure that the catalyst is evenly attached to obtain the mixed material; (3) Hot pressing and remolding: Place the mixed material into the mold of the flat vulcanizing machine (the mold cavity is dumbbell-shaped and conforms to ASTM D412 standard); set the hot pressing temperature to 150℃ and the pressure to 10 MPa; preheat for 3 minutes, and then hold the pressure for 15 minutes; after the pressure is held, maintain the pressure, cool with water to below 60℃, open the mold and take out the remolded dumbbell-shaped sample.

[0043] Performance testing was conducted in accordance with Example 2; The performance of the recycled molding specimens was compared with that of the original materials (the average value of the film from Example 1 and the sheet from Example 2), and the results are shown in Table 1.

[0044] Table 1 The results in Table 1 show that: The mechanical properties (strength, elongation) of the recycled molding specimens remained good (>88%), indicating successful reorganization of the dynamic network. The hardness of the recycled molding specimens increased slightly, possibly due to partial changes in the network structure or fine-tuning of the filler distribution during reprocessing. Electrical properties showed some degradation (resistivity increased by 40%, GF value decreased by 12%), which may be due to the breakage of some CNTs or AgNWs or irreversible changes in the conductive network structure during high-temperature and high-pressure reprocessing; however, the degradation was within acceptable limits, and the material still possessed good sensing capabilities. Therefore, this embodiment confirms that the silicone composite material for artificial skin in humanoid robots provided by this invention has feasible closed-loop recycling potential. By optimizing reprocessing conditions (such as reducing temperature and shortening time) or supplementing with a small amount of fresh conductive filler, it is expected that the retention rate of the electrical properties of the recycled material can be further improved.

[0045] Comparative Example 1 The film preparation conditions and steps are the same as in Example 1, except that Maleimide-PDMS-Thiol is replaced with commercially available Silane-PEG-Maleimide (silane-polyethylene glycol-maleimide).

[0046] The performance testing of the thin film was conducted with reference to Example 1, and the results are as follows: Shore A hardness is 5 A; tensile strength is 2.1 MPa; elongation at break is 940%; volume resistivity is 8 × 10⁻⁶. 3 Ω·cm; GF value at 200% strain is 21.

[0047] This shows that while using the more rigid Silane-PEG-Maleimide significantly improves the mechanical properties of the film, it significantly degrades its electrical properties.

Claims

1. A silicone composite material for artificial skin of humanoid robots, characterized in that, The composite material consists of a dynamically cross-linked silicone matrix and a multifunctional conductive sensing network, and has a functionally graded or multilayer structure. The dynamically cross-linked silicone matrix is ​​composed of a siloxane polymer network containing reversible covalent bonds or supramolecular interactions. The multifunctional conductive sensing network is a three-dimensional interconnected and oriented network structure formed by surface-modified one-dimensional or two-dimensional nano-conductive fillers in the dynamically cross-linked silicone matrix through external field-induced assembly.

2. The silicone composite material for artificial skin of a humanoid robot according to claim 1, characterized in that, The dynamically cross-linked silicone matrix comprises two dynamic networks with different response characteristics: the first network is composed of dynamic covalent bonds; the second network is composed of thermosensitive supramolecular forces.

3. The silicone composite material for artificial skin of a humanoid robot according to claim 2, characterized in that, The dynamic covalent bonds in the first network are selected from at least one of the following: dynamic covalent bonds based on transesterification reactions, reversible covalent bonds based on Diels-Alder addition reactions, and dynamic covalent bonds based on disulfide bond exchange.

4. The silicone composite material for artificial skin of a humanoid robot according to claim 2, characterized in that, The thermosensitive supramolecular forces in the second network are selected from at least one of the following: quadruple hydrogen bonds based on 2-ureido-4[1H]-pyrimidinone, supramolecular interactions based on coordination bonds, and forces based on the melting-crystallization phase transition of crystalline soft segments.

5. The silicone composite material for artificial skin of a humanoid robot according to claim 1, characterized in that, The insulating polymer layer is discontinuously distributed on the filler surface.

6. The silicone composite material for artificial skin of a humanoid robot according to claim 1, characterized in that, The conductive filler in the multifunctional conductive sensing network is a core-shell hybrid filler.

7. A method for preparing a silicone composite material for artificial skin of a humanoid robot according to any one of claims 1-6, characterized in that, Includes the following steps: (1) Surface modification and pretreatment of conductive fillers: The selected nano-conductive fillers are surface functionalized to introduce reactive functional groups that can chemically bond or strongly interact with the dynamic silica network. (2) Preparation of dynamically crosslinked silicone prepolymers: Synthesize siloxane prepolymer compositions containing reversible covalent precursors or supramolecular units; (3) Preparation of filler-matrix composite slurry: The modified conductive filler obtained in step (1) is uniformly dispersed in the dynamic cross-linked silicone prepolymer obtained in step (2) to form a processable composite slurry; (4) External field-induced directional assembly and molding: The composite slurry obtained in step (3) is injected or coated onto the molding mold or substrate. Before or during the curing process of the slurry, an external field is applied to induce the conductive filler to be oriented and assembled in a preset direction to form an orderly conductive network. (5) Dynamic cross-linking curing and post-treatment: Under suitable temperature or light conditions, the prepolymer in step (4) undergoes a cross-linking reaction to form a dynamic cross-linking network, while locking the ordered structure of the filler.

8. The method for preparing artificial skin silicone composite material for humanoid robots according to claim 7, characterized in that, The surface functionalization modification described in step (1) includes grafting a polymer brush with "double-ended anchoring and intermediate flexibility" onto the surface of the conductive filler.

9. The method for preparing artificial skin silicone composite material for humanoid robots according to claim 7, characterized in that, The external field mentioned in step (4) is at least one of a magnetic field, an electric field, or a shear field.

10. A humanoid robot's biomimetic skin, characterized in that, The humanoid robot's biomimetic skin is made of the silicone composite material according to any one of claims 1-6, or of the material prepared by the method according to any one of claims 7-9.